2018
DOI: 10.1101/280917
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wheat shovelomics II: Revealing relationships between root crown traits and crop growth

Abstract: Optimization of root system architecture represents an important goal in wheat breeding. Adopting new field methods for root phenotyping is key to delivering this goal. A novel ‘shovelomics’ method was applied for phenotyping root crown traits to characterize the Savannah x Rialto doubled-haploid (DH) population in two field experiments under irrigated and rain-fed conditions. Trait validation was carried out through soil coring on a subset of 14 DH lines and the two parents. We observed that drought reduced g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Given the results reported here, the most effective way to screen for mature root depth may be the use of high-throughput, field-based techniques. Methods in development include high-throughput soil coring methods ( Wasson et al ., 2014 , 2016 ), mature root crown analysis methods ( Slack et al , 2018 , Preprint), and non-destructive, above-ground indicators of crop ‘health’ after flowering such as cooler canopy temperature and/or high normalized difference vegetation index ( Li et al , 2019 ). These have been shown to be effective to identify higher yielding wheat genotypes with deeper roots, but further work remains to ascertain the most efficient and effective phenotyping method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the results reported here, the most effective way to screen for mature root depth may be the use of high-throughput, field-based techniques. Methods in development include high-throughput soil coring methods ( Wasson et al ., 2014 , 2016 ), mature root crown analysis methods ( Slack et al , 2018 , Preprint), and non-destructive, above-ground indicators of crop ‘health’ after flowering such as cooler canopy temperature and/or high normalized difference vegetation index ( Li et al , 2019 ). These have been shown to be effective to identify higher yielding wheat genotypes with deeper roots, but further work remains to ascertain the most efficient and effective phenotyping method.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotyping mature roots to depth in the field is possible ( Wasson et al , 2014 ; Rich et al , 2016 ); however, it is constrained by the time wheat takes to reach maturity and the strong influence of the soil physical and chemical conditions on the mature root system phenotype ( Manschadi et al , 2006 ; Wasson et al , 2012 ; Rich and Watt, 2013 ). Additionally, affordable and accurate high-throughput direct and indirect root phenotyping methods for the field are still in development ( Wasson et al , 2016 ; Slack et al , 2018 , Preprint; Li et al , 2019 ). The development of high-throughput controlled-environment seedling root screens presents an opportunity to, at least partially, circumvent the current lack of field screening options ( Richards et al , 2010 ; Wasson et al , 2012 ; Watt et al , 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous simulations determined that a shallow root system is more favourable in this type of environment (reviewed in Izanloo et al, 2008), which contrasts with the root system architecture (RSA) of R112+, found to be characterized by increased seminal root angle, total root length and root dry weight . Under drought conditions, a widened root angle and deeper roots were found to be crucial adaptive mechanisms associated to yield increases in rice (Uga et al, 2013;Ahmadi et al, 2014) and wheat (Lopes and Reynolds, 2010;Manchadi et al, 2006;Slack et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Shovelomics quantifies traits on the washed 'root crown'. Root number, growth, and angle were measured in various species and soil conditions [62][63][64][65]. Digital imaging of root traits, root estimator for shovelomics traits, and the multiperspective imaging platform [66][67][68] standardize and increase the root measurements captured from multiple images of the same root crown.…”
Section: Field Phenotypingmentioning
confidence: 99%